2016
DOI: 10.1177/0042098015598745
|View full text |Cite
|
Sign up to set email alerts
|

Do rural migrants ‘float’ in urban China? Neighbouring and neighbourhood sentiment in Beijing

Abstract: Urban China reached 50% of the nation's population by 2010, mainly as a result of massive ruralurban migration. There is substantial evidence of their social marginality in terms of occupational and housing opportunities. Here we ask about their incorporation into the neighbourhoods where they live. Rural migrants are called the 'floating population' in China, suggesting that their residence in the city is only temporary and that they are unlikely to develop strong local ties. This study contrasts the neighbou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
102
4
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 101 publications
(110 citation statements)
references
References 50 publications
2
102
4
2
Order By: Relevance
“…The transition from a planned to market-led economy has fundamentally changed how Chinese urban citizens interact with each other (Hazelzet & Wissink, 2012;Wu & Logan, 2015). The burgeoning middle class, who are the primary residents of commodified housing stock, rely instead on social ties outside of the neighbourhood and are less involved with neighbours (Li et al, 2012, p. 249).…”
Section: Migrant-local Social Relations and Neighbourhood Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transition from a planned to market-led economy has fundamentally changed how Chinese urban citizens interact with each other (Hazelzet & Wissink, 2012;Wu & Logan, 2015). The burgeoning middle class, who are the primary residents of commodified housing stock, rely instead on social ties outside of the neighbourhood and are less involved with neighbours (Li et al, 2012, p. 249).…”
Section: Migrant-local Social Relations and Neighbourhood Interactionmentioning
confidence: 99%
“…Research so far has paid considerable attention to the frequency of local interactions ranging from visiting each other, mutual support and neighbourly communications (Forrest & Yip, 2007;Wang et al, 2016;Wu & Logan, 2015). However, less focus has been placed on the affective side of neighbourhood relations.…”
Section: Migrant-local Social Relations and Neighbourhood Interactionmentioning
confidence: 99%
“…Additionally, Wang et al (2017c) found that there is a large portion of commodity residents who believe that residents are taking good care of each other and consider their neighbours as trustworthy. Recent studies also find that neighbouring is an important form of social networking for rural migrants (Liu et al, 2017a;Liu et al, 2017b;Wu & Logan, 2016). Compared to native residents whose social networks are no longer bound by the locality (Hazelzet & Wissink, 2012), rural migrants only have a limited social network in the city and rely on neighbourly relations as a means to receive support and exchange information (Wu & Logan, 2016).…”
Section: Neighbouring and Community Participation In Chinese Citiesmentioning
confidence: 99%
“…Recent studies also find that neighbouring is an important form of social networking for rural migrants (Liu et al, 2017a;Liu et al, 2017b;Wu & Logan, 2016). Compared to native residents whose social networks are no longer bound by the locality (Hazelzet & Wissink, 2012), rural migrants only have a limited social network in the city and rely on neighbourly relations as a means to receive support and exchange information (Wu & Logan, 2016). Rural migrants engage in both in-group neighbourly relations with fellow migrants and intergroup neighbourly relations with native neighbours (Wang et al, 2016).…”
Section: Neighbouring and Community Participation In Chinese Citiesmentioning
confidence: 99%
“…Some recent works on the changing demographics, ambitions and identifications of migrants include Connelly et al . (); Zhu and Chen (); Chen and Wang (); Wu and Logan (); and Chen and Fan (); Nalini et al (2017).…”
mentioning
confidence: 99%